2014
DOI: 10.3758/s13414-014-0777-1
|View full text |Cite
|
Sign up to set email alerts
|

Listening to music reduces eye movements

Abstract: Listening to music can change the way that people visually experience the environment, probably as a result of an inwardly directed shift of attention. We investigated whether this attentional shift can be demonstrated by reduced eye movement activity, and if so, whether that reduction depends on absorption. Participants listened to their preferred music, to unknown neutral music, or to no music while viewing a visual stimulus (a picture or a film clip). Preference and absorption were significantly higher for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 54 publications
(50 reference statements)
4
27
4
Order By: Relevance
“…Only blink frequency was affected by music, showing that participants blinked more often with music than without. Contrary to other research, there were also no effects on eye movement parameters (Mera & Stumpf, 2014;Schäfer & Fachner, 2015), and we did not find systematic effects of music on viewers' scene perception as suggested by Auer et al (2012). Our results are more in line with Coutrot and Guyader (2014) and Smith (2014), who found no influence of non-diegetic sounds on eye movements, using speech, natural sounds, and music.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Only blink frequency was affected by music, showing that participants blinked more often with music than without. Contrary to other research, there were also no effects on eye movement parameters (Mera & Stumpf, 2014;Schäfer & Fachner, 2015), and we did not find systematic effects of music on viewers' scene perception as suggested by Auer et al (2012). Our results are more in line with Coutrot and Guyader (2014) and Smith (2014), who found no influence of non-diegetic sounds on eye movements, using speech, natural sounds, and music.…”
Section: Discussioncontrasting
confidence: 99%
“…One of the few experiments investigating the impact of music on eye movements was carried out by Schäfer and Fachner (2015). Participants watched pictures and video clips while listening to their favourite music, unknown music, or no music.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further research using eye-tracking found that viewers attend differently to details in images depending on their music-induced emotions [ 32 , 33 ]. When watching visual stimuli with music or in silence in an experimental study, the music reduced eye movements in terms of longer fixations, a higher number of blinks and fewer saccades, arguably related to a shift of attention to an “inner world” ([ 34 ], p. 556). Music may thus induce states of contemplation and attention to inner processes.…”
Section: Introductionmentioning
confidence: 99%
“…The evidence of implicit musical influence on eye movement timing is more limited. A study by Schäfer and Fachner (2014), eye-tracked participants who free-viewed either a static scene of a house, or a first person film of a car driving down an empty road. The visuals were presented with background music or in silence.…”
mentioning
confidence: 99%